Knowledge and practice among nurses on management of tuberculosis in a teaching hospital - Hng, Siew Hong; Siti Nabihah S; Siti Nabilah S (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Tuberculosis (TB) has become a worldwide public concern with 10.4 million new cases reported in 2015 and 1.4 million deaths. More importantly, an increase in trend in TB incidence among healthcare workers has become a major concern. Therefore, the present study was conducted to explore the knowledge and practice towards TB and the factors associated with it among nurses in a teaching hospital. The present study used cross-sectional design and stratified sampling method. A total of 275 nurses in a teaching hospital participated in this study. The knowledge and practice on management of TB was measured using a structured questionnaire. Majority of the respondents had good knowledge and practice on management of TB represented by 70.2% and 63.3%, respectively. However, knowledge gap (1.8%) and practice gap (0.4%) were identified in method of sputum collection. Work place setting was the only demographic factor found significantly associated with level of knowledge and practice (p=0.028). Level of knowledge and practice on management of TB identified among nurses was not associated with many socio-demographic factors. Nurses as frontline healthcare workers are at high risk of being exposed due to frequent contact with various patients especially those who are undiagnosed and TB suspect patients. Hence, implementation of TB Infection Control (TBIC) measures is important to minimize the risk of infection and cross-infection within hospital.